Pengaruh Tingkat Aksesibilitas terhadap Penggunaan Lahan di Jembatan Youtefa, Kota Jayapura: Studi Kasus: Ruas Jalan Hamadi – Jalan Holltekamp - Dimas Naufal Bilalramadhan; Monita Yessy Beatrick Wambrauw; Lisa Agnesari (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
Accessibility bags are an easier size of location to be reached from other locations through the transport system. Therefore, the youtefa bridge, inaugurated in 2019, would be the goal of accessibility of the tami outlandline district to the southern jayapura district as well as vice versa. Over time, the presence of youtefa bridge has had an effect on land use along holtekamp's coast. Changes in resource use, such as cafes building, resort or resort, and OARS for the activities of national xx sports week are a new problem because land that should be reduced to parks is turned into a generating area. The purpose of this study is to find the LHR comparison and to explain land use comparisons in 2019 and 2021, as well as to explain the relation between accessibility to land use at the research site. The approach used in this study is the cumulative and quantitative approach. The LHR conditions on the research site in 2021 saw an increase of 1,250 SMP per hour or twice that of 2019. While land use in 2021 is 28.4 ha. For accessibility tas effect on land use, a value of 1.53 on which it falls in a high category. The function of land governance in the scope of the research site or youtefa bridge is not all that is cultivated. It is necessary to consider how the region functions in order to match its land requirements.